A controversial topic, depopulation. Perceptions of Second Year ESO students in different socio-educational contexts: Rural/urban and Segovia/Madrid - Cabañero Martín, Víctor Manuel (Clio. History and History Teaching, 2024)
This article presents the initial phase of a research project examining depopulation as a controversial topic from an interdisciplinary perspective, emphasising the role of history in understanding this issue. This phase involves a questionnaire designed to explore the perceptions of 2nd-year secondary school students regarding the study of history, its relevance to current issues, their views on depopulation, and their opinions on stereotypes. Three questions were analysed to identify perceptual differences between urban and rural students, as well as between schools based on their geographical location. Using a mixed-methods approach, the study identifies differences in perception among students from Segovia and Madrid, as well as between the schools.
Keywords: controversial topic; depopulation; student perception; urban/rural differences; history education